Predicting Successful Aging at One Hundred Years of Age - Araújo, Lia (2016)
The present study is based upon a multidimensional model of successful aging. It aims to identify subgroups of centenarians sharing communalities in successful aging profiles, and determine the role of sociodemographic factors and psychological, social, and economic resources on successful aging.